2014
DOI: 10.3345/kjp.2014.57.4.186
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of C-reactive protein in response to macrolides in children with macrolide-resistantMycoplasma pneumoniaepneumonia

Abstract: PurposeThe prevalence of macrolide-resistant Mycoplasma pneumoniae (MRMP) has increased worldwide. The aim of this study was to estimate the proportion of MRMP in a tertiary hospital in Korea, and to find potential laboratory markers that could be used to predict the efficacy of macrolides in children with MRMP pneumonia.MethodsA total of 95 patients with M. pneumoniae pneumonia were enrolled in this study. Detection of MRMP was based on the results of specific point mutations in domain V of the 23S rRNA gene.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 28 publications
3
22
1
Order By: Relevance
“…CRP is correlated with the degree of MPP and plays a role in estimating the severity of the disease. Seo et al19 reported that serum CRP could be a useful marker for predicting the efficacy of macrolides in MRMP. In this study, the levels of CRP were correlated with the severity of chest radiographic manifestations; however, the diagnostic value was poor.…”
Section: Discussionmentioning
confidence: 99%
“…CRP is correlated with the degree of MPP and plays a role in estimating the severity of the disease. Seo et al19 reported that serum CRP could be a useful marker for predicting the efficacy of macrolides in MRMP. In this study, the levels of CRP were correlated with the severity of chest radiographic manifestations; however, the diagnostic value was poor.…”
Section: Discussionmentioning
confidence: 99%
“…The following variables were extracted: patient characteristics (e.g., age, sex), acute neurological and non-neurological symptoms, duration of prodromal non-neurological symptoms prior to the onset of neurological symptoms, presence or absence of macrolide (clarithromycin) resistance defined by the absence of defervescence within 72 h after initiation of clarithromycin [11], laboratory data, including white blood cell (WBC) count in the peripheral blood, serum levels of C-reactive protein (CRP) and sodium, presence or absence of pleocytosis in CSF, findings on electroencepharography (EEG), initial and follow-up neuroimaging, duration till recovery of clinical symptoms and of abnormal findings on neuroimaging, and outcome including neurological sequelae.…”
Section: Methodsmentioning
confidence: 99%
“…Based on a review of the literature, there are a few reports on the role of LDH, C-reactive protein, and ESR in refractory M. pneumoniae pneumonia, but they are limited to case series. 4,13,14 In this study, we explored whether LDH, Creactive protein, and ESR are potential laboratory markers that could be used to predict refractory M. pneumoniae pneumonia in a large sample.…”
Section: Introductionmentioning
confidence: 99%